Safety and efficacy of bridging radiation therapy prior to CD19 CAR T for non-Hodgkin lymphoma: a systematic review and meta-analysis - Mohammad Alhomoud; Rahma Ibrahim; Michelle Demetres; Kai Rejeski; Michael Scordo; Roni Shouval; Tobias Tix; Jeremie Martinet; Michelle Foley; Alexandra Gomez-Arteaga; Tsiporah Shore; Paul Pagnini; et al. (Haematologica, 2025)
Bridging radiation therapy (BRT) is increasingly utilized prior to CART19 in NHL patients. However, its impact on CART19 outcomes is not established. We conducted a systematic review and meta-analysis to estimate the safety and efficacy of BRT prior to CART19 therapy. A comprehensive search was performed in databases from inception to October 2024. We identified 18 studies encompassed 538 adult NHL patients who received BRT prior to commercial CART19. Random-effect models were applied to explore meta-analysis outcomes. DLBCL was the most common diagnosis (73%), and axicabtagene ciloleucel was the most utilized product (67%). Bulky disease was present in 37%. Median BRT dose was 30 Gy delivered comprehensively to all sites of PET avid disease in 76% of cases. ORR to CART19 was 78.9%. At 1 year, PFS was 54.6% while OS was 71.2%. All-grade CRS was 80% while all-grade ICANS was 39.4%. Grade 3/4 CRS was 3.6% and grade 3/4 ICANS was 10.6%. Sensitivity analyses including studies with bulky disease and excluding studies with patients who also received systemic bridging therapy, demonstrated consistent results compared to the main study findings. Sub-group meta-regression showed similar results in studies that utilized BRT only compared to studies that utilized combined-modality treatment. In conclusion, this metaanalysis found that BRT use prior to CART19, whether as a standalone approach or in combination with systemic therapy, does not increase toxicity or compromise the efficacy of CART19 therapy in NHL. Furthermore, use of BRT is associated with low rate of CRS, even in patients with bulky disease.